The History and Sociology of Genocide : Analyses and Case Studies - Chalk, Frank Robert, 1937-; Jonassohn, Kurt. (London : Yale University press, 1990)
Includes bibliographical references (p. 430-461).
Published in cooperation with the Montreal Institute for Genocide Studies.
Includes bibliographical references (p. 430-461)
Keywords: Genocide -- History; Genocide -- Case studies